Euro Area Money Demand : Measuring the Opportunity Costs Appropriately - Levy, Joaquim (IMF Working Papers; Working Paper, 2001)
The existence of a well-specified and stable relationship between money and prices has long been perceived as a prerequisite for the use of monetary aggregates in the conduct of monetary policy. This paper contributes to the ongoing discussion about the stability of euro area money demand by constructing an own rate of return on euro area M3 and by analyzing its implications in a standard money demand system. Over the sample period, one cointegrating vector relating real M3, real GDP and the spread between the short-term interest rate and the own rate of M3 can be identified and interpreted as a long-run euro area money demand equation. A dynamic money demand system is subsequently estimated. Standard diagnostics stability tests and out-of-sample forecasts confirm the good statistical performance of the model.